Pengembangan Bahan Ajar Matematika Berbasis Kontekstual (CTL) Materi Bilangan Bulat Kelas IV Sekolah Dasar Negeri 3 Rensing Tahun Pelajaran 2014/2015 - Yuliana Susanti (PALAPA, 2016)
The development of research aims to develop products in the form of teaching materials contextually based on a math class IV SDN No 03 Rensing in the academic year 2014/2015. This study is a research and development (Research and Development). The development of research development model Borg and Gall were conducted with five stages, namely the analysis of needs, planning, development of draft products, field trials, product revision. Data collection methods used in the research are the development of student questionnaire responses and test student learning outcomes. The subjects to be tested in this study were all fourth grade students of SDN 3 Rensing who was 22 people. Products developed in the form of books students with contextual approach, assessment in terms of materials and appearance. Book value of the validation results of students in terms of material is 3.37, while the display is 3.12 s`egi the category of "valid" and unfit for use by the revision of each validator. The percentage of students who responded positively to the students 'books reached 54.6% and the data obtained from the test results of the students' learning reached 77%. The coefficient of determination (R2) = 0.69. This means that 69% influence the development of teaching materials mathematics contextually based on student learning outcomes. It can be concluded in the study of mathematics teaching material development using a model based contextual Borg and Gall said Valid and Effective to learning the material integers grade IV SDN 3 Rensing in the academic year 2014/2015.